“Whatever is in the ARVs, is Also in the PrEP” Challenges Associated With Oral Pre-exposure Prophylaxis Use Among Female Sex Workers in South Africa - Makhakhe, Nosipho Faith; Sliep, Yvonne; Meyer-Weitz, Anna (Frontiers in Public Health, 2022)
Background: The national policy on oral pre-exposure prophylaxis (PrEP) for female sex workers (FSWs) was instituted in South Africa in 2016. FSWs were targeted for PrEP due to a Human immunodeficiency virus (HIV) prevalence of 57.7%, which is higher than the prevalence of 19.07% among the general population. Research from demonstration studies has shown that uptake of PrEP has been slower than anticipated, and the purpose of this study was to explore barriers to the uptake of PrEP among FSWs. Methods: An in-depth qualitative study was conducted with 39 participants, 30 individual participants, and nine focus group participants. Eleven participants consisted of peer educators and two health workers from a sex work and PrEP distribution organization, the rest of the participants (26) were FSWs. Results: The majority of participants mentioned that little distinction was made between PrEP and antiretrovirals (ARVs) taken by FSWs living with HIV. PrEP was not distributed through public health care facilities, and health workers unknowingly labelled PrEP as ARVs. Consequently, health workers seen as experts created suspicion and contributed to the mistrust of PrEP among FSWs due to mixed messages, and equating PrEP to ARVs reduced uptake. Furthermore, failure to make a clear distinction between oral PrEP and ARVs resulted in accusations of lying, denialism, and deception levelled at users of PrEP by FSWs using ARVs, and sometimes by clients and intimate partners. FSWs using PrEP reported feeling stigmatized and thrust into interpersonal conflict with their peers after choosing PrEP, leading to broken relationships, and some resorting to taking PrEP privately or discontinuing PrEP altogether. Conclusion: PrEP as an ARV targeted for the prevention of HIV among high-risk groups was found to be stigmatizing. The distinctive use of PrEP and ARVs should be correctly explained to users to minimize confusion, enable differentiation and reduce interpersonal conflict. Cohesion among sex work organizations and public health care facilities is needed to disseminate the correct knowledge on PrEP. A non-stigmatizing approach to the distribution of PrEP may serve to increase uptake and adherence.